Active Disturbance Rejection Control of a Coupled-Tank System. (8th July 2018) - Abukhadra, Fayiz
Abstract : In process industries, liquid is pumped and stored in interacting coupled tanks. The liquid level in these tanks must be accurately controlled. This study aims to investigate the performance of the active disturbance rejection control method in controlling a coupled-tank system. A mathematical model of the coupled-tank system is derived to facilitate a simulation study. Assuming that the water level in the second tank is the only measured state, an extended observer with time-varying parameters estimates the second state and the total disturbances of the system. The system is then regulated using a time-varying feedback controller. The results show the effectiveness of the method in improving the time domain measures and the disturbance rejection compared to other controllers.